Ethnic relations and politics in the community of South Tanjung Balai Subdistrict after the 2016 conflict - Maria Br Sianipar; Indra Fauzan (Priviet Social Sciences Journal, 2025)
The conflict that occurred in Tanjungbalai in 2016 was a complex phenomenon influenced by several factors, including ethnic, religious, and political factors. This conflict was triggered by differences in views and interests between groups, as well as economic inequality that worsened the situation. Therefore, this study aims to explain and describe the relationship between ethnicity and changes in local political policies after the conflict. This study uses a qualitative descriptive method, namely research that aims to be based on data obtained in the field and is accurate and in the form of interviews with the specified informants. To strengthen the explanation in this study, the researchers used ethnic political theory, conflict theory, and ethnic theory. Based on the methods and theories used, the results of this study show that the ethnic and political relations of the people in Tanjungbalai are currently running well. However, some 5% of Chinese people are still very vulnerable and require systematic and sustainable efforts to restore relations between different ethnic groups. Until now, the efforts of the Tanjungbalai city government have been very careful in maintaining religious harmony in Tanjungbalai so that this conflict does not happen again.